Charmonium suppression by gluon bremsstrahlung in p-A and A-B collisions - Hüfner, Jörg; He, Yong-Bin; Kopeliovich, Boris Z. (The European physical journal. A, Hadrons and nuclei, 2000)
Prompt gluons are an additional source for charmonium suppression in nuclear collisions, in particular for nucleus-nucleus collisions. These gluons are radiated as bremsstrahlung in N-N collisions and interact inelastically with the charmonium states while the nuclei still overlap. The spectra and mean number <ng> of the prompt gluons are calculated perturbatively and the inelastic cross section σabsΨg is estimated. The integrated cross sections σ(A B →J/ψX) for p-A and A-B collisions and the dependence on transverse energy for S-U and Pb-Pb can be described quantitatively with some adjustment of one parameter <ng>σabsΨg.